Effect of different varieties of rosemary (Rosmarinus officinalisi) plant extracts on in vitro methane production of Eragrostis curvula hay - Hassen, Abubeker (University of Pretoria, 2025)
Dissertation (MSc (Animal Science))--University of Pretoria, 2024.